Teratoma Growth Retardation by HDACi Treatment of the Tumor Embryonal Source - Krasic, Jure (Cancers (Basel), 2020)
SIMPLE SUMMARY: Testicular germ cell tumors are the most common neoplasms in young male populations, with a rising incidence. Among them, teratomas may often be very aggressive and resistant to therapy. Our aim was to investigate the impact of two potential anti-tumor epigenetic drugs (Valproate and Trichostatin A) in a mammalian model of teratoma development from an early trilaminar mouse embryo. Both drugs applied to the embryonic tissue had a significant negative impact on the teratoma growth in a three-dimensional in vitro culture. However, Trichostatin A did not diminish some potentially dangerous features of teratomas in contrast to Valproate. This research is an original contribution to the basic knowledge of the origin and development of teratomas. Such knowledge is necessary for envisioning therapeutic strategies against human testicular tumors. ABSTRACT: Among testicular germ cell tumors, teratomas may often be very aggressive and therapy-resistant. Our aim was to investigate the impact of histone deacetylase inhibitors (HDACi) on the in vitro growth of experimental mouse teratoma by treating their embryonic source, the embryo-proper, composed only of the three germ layers. The growth of teratomas was measured for seven days, and histopathological analysis, IHC/morphometry quantification, gene enrichment analysis, and qPCR analysis on a selected panel of pluripotency and early differentiation genes followed. For the first time, within teratomas, we histopathologically assessed the undifferentiated component containing cancer stem cell-like cells (CSCLCs) and differentiated components containing numerous lymphocytes. Mitotic indices were higher than apoptotic indices in both components. Both HDACi treatments of the embryos-proper significantly reduced teratoma growth, although this could be related neither to apoptosis nor proliferation. Trichostatin A increased the amount of CSCLCs, and upregulated the mRNA expression of pluripotency/stemness genes as well as differentiation genes, e.g., T and Eomes. Valproate decreased the amount of CSCLCs, and downregulated the expressions of pluripotency/stemness and differentiation genes. In conclusion, both HDACi treatments diminished the inherent tumorigenic growth potential of the tumor embryonal source, although Trichostatin A did not diminish the potentially dangerous expression of cancer-related genes and the amount of CSCLC.